Does regulatory convergence shape banking resilience in Africa? - Minyahil Alemu Haile; Jayamohan M.K.; Wondaferahu Mulugeta (Heliyon)
This study examines the effects of Basel III regulatory harmonization on banking stability across 21 African nations from 2011 to 2022, using a system-GMM estimation to address endogeneity and enhance causal interpretation. Stability is operationalized through Z-scores, non-performing loan ratios, and weighted composite indices, offering a robust, multi-dimensional perspective on systemic resilience. Findings suggest that Basel III compliance enhances stability across key metrics, yet reveal a trade-off wherein liquidity buffers may detract from operational efficiency unless optimally rectified to local conditions. Furthermore, institutional quality, particularly governance and property rights protections, amplifies regulatory impact, supporting transparency and resilience within the banking system. It is, thus, imperative to fortify regulatory and governance structures, optimizing financial resilience to underpin sustainable economic growth across the region. By integrating risk-weighted Tier 1 capital convergence within stability models, this research makes a substantial contribution to banking literature, refining stability frameworks and paving the way for deeper exploration of Basel III elements to provide robust, evidence-based insights into regulatory impacts on banking resilience.